IMPLEMENTASI KEBIJAKAN KOMUNIKASI SOSIAL TNI UNTUK MENGATASI PAHAM RADIKALISME DI WILAYAH KODAM - Wibisono Poespitohadi; Susilo Susilo; Wahyu Wiyani; Chandra Dinata; Akbar Pandu Dwinugraha (Journal Publicuho, 2024)
This research aims to evaluate the implementation of the TNI's Social Communication policy in addressing radicalism in the Kodam III/Siliwangi area, focusing on the effectiveness of the programme, available resources, as well as obstacles and solutions encountered in its implementation. The research was conducted using a case study approach. Data collection techniques were carried out through interviews with informants, namely the Assistant Kasdam III/Siliwangi Cq. Operations Assistant and Territorial Assistant, Bakesbangpol Linmas of West Java Province, Regional Office of the Ministry of Religion and Ministry of Law and Human Rights of West Java Province. This research reveals that the implementation of TNI social communication faces challenges in overcoming radicalism, including a lack of understanding of the mechanisms of radicalism and a lack of participation in deradicalisation initiatives initiated by BNPT. Other factors affecting policy implementation are resource considerations such as personnel, equipment, and financial resources. Improving the capability of local command structures and coordination with relevant partners is required to successfully tackle radicalism. Comprehensive awareness of local culture and the creation of Standard Operating Procedures (SOPs) involving all relevant parties in the regions are also important to improve the effective identification and prevention of radicalism.